ASSESSMENT OF GENOME-WIDE EVOLUTIONARY RELATIONSHIP AND CHARACTERIZATION OF GhFPF1 FAMILY IN G. HIRSUTUM - A. H. Jarwar; X. Wang; W. Long; A. Ahmad; N. Mangi; Q. Ma; F. Shuli (Journal of Animal and Plant Sciences, 2019)
A flowering promoting factor 1 was first cloned from Arabidopsis, and it is a model type of species which have revealed a network of regulatory association between proteins that integrate and transduce environmental and developmental signals to advanced or inhibit the transition to flowering. FPF1 homologus sequences were examined from diploid G. arboreum L. genome (A-genome, n=13), and Gossypium raimondii L. (D-genome, n=13) data base. There are two orthologus genes are propose that distinctions at amino acid and nucleic acid levels were not significance because of degeneracy of codon. Atleast 6 genes of FPF1 were obtained from cultivated allotetraploid species Gossypium hirsutum L (genome AD, n=26). Analysis of six genes from various tissues discloses that this type of gene family shows that expression level of tissue specific is very strong. In previous studies in Arabidopsis it shows significantly suppressed Flowering Locus C and activated in APETALA 1 expression were stimulate by over expression of GhFPF1 in the Arabidopsis.
Keywords: GhFPF1; wild type; transgenic; G-Protein